The pillars of the earth - Follett, Ken. (New York : Morrow, 1989)
A story of passion and idealism, which describes a group of men and women in the Middle Ages whose destinies are fatefully linked with the building of a cathedral. In a country torn by civil war, two generations struggle to rise above their primitive circumstances and create something beautiful.
N/A ll
Keywords: Cathedrals -- Fiction; Middle Ages -- Fiction; Great Britain -- History -- Stephen, 1135-1154 -- Fiction; Historical fiction; Epic fiction